Observed radar and environmental properties of United States warm season bowing convective systems, 2003-2004 - Quelet, Paul, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 2006)
This study examines radar-indicated structures and environments of bowing convective systems in the United States during the warm seasons of 2003 and 2004 (April-December). The bowing process is defined as local acceleration of a convective cell or cells on the convex leading edge of a convective system to form an "arch" or "bow"-shaped line. This study perused data for each day of the two-year time period and investigated the bowing process using 2-km national radar reflectivity composite data. This procedure yielded 381 bowing convective systems, the majority of which occurred from May to July. The locations of these systems show a distribution similar to past studies of warm season derechos with two primary corridors: one in the Upper Great Plains, and secondarily, a maximum toward the Central/Southern Great Plains. The entire population of bowing convective systems is classified into five modes, based on their differences in initial convective cell structures, convection evolution processes, locations, diurnal beginning and ending times, severe weather reports, and kinematic/thermodynamic environments. These modes are termed bow echo/extensive stratiform, bow echo/minimal stratiform, bowing squall line, multiple bowing squall lines, and bowing single cell. Bow echoes/extensive stratiform exhibited trailing stratiform precipitation and most commonly evolved from groups of cells. Bow echoes/weak stratiform showed very limited trailing precipitation usually evolving from the merging of supercells with ordinary or multicells. Single and multiple bowing squall lines most often evolved from trailing stratiform mesoscale convective systems. An assessment of bowing convective line lengths and movement speeds was performed. Bowing convective line lengths of bow echoes/extensive stratiform and bow echoes/weak stratiform ranged from 40-110 km. Bowing squall lines and multiple bowing squall lines had convective lines segments between 110-225 km while bowing single cells were observed between 20-40 km. The bowing convective systems observed in this study exhibit a preferred range of speeds between 10 and 24 m s-1. This study also examines the characteristics of trailing stratiform precipitation in bowing convective systems. Pre-existing or convectively generated trailing precipitation tends to enhance the longevity of a bowing convective system. In some cases an enhanced trailing stratiform precipitation region was arranged in a perpendicular fashion behind the bowing convective systems while in other cases the trailing precipitation sustained a wide stratiform precipitation transition zone with minimal precipitation separating a bowing convective line from moderate-to-heavy stratiform precipitation. The latter precipitation pattern showed a strong tendency to increase system longevity. Examination of convection properties related to bowing convective systems demonstrates the importance of identifying supercells and multiple supercells evolving or interacting with exterior convection to initiate bowing convection. Convective cell mergers, which also usually aid in the initiation of bowing convection, are strongly preferred near the resultant apex. Observations of ensuing bowing convective lines display a preference toward strong convection that is nearly homogeneous (slabular as opposed to cellular) in the along-line direction. It was further observed that warm season bowing convection is favored in hybrid synoptic boundary forcing environments (moving parallel to or initiating on a synoptic boundary), while bowing convective systems forced by no synoptic boundary is of secondary importance. Also, bowing convective systems that moved parallel to synoptic boundaries exhibited enhanced longevities. No bowing convective system that traversed a synoptic boundary continued for longer than three hours. Finally, this study classifies severe weather production from bowing convective systems into four spatial patterns based on their shape and the nature of their effects. These are termed narrow apex swath, widespread high winds, widening swath, and destructive rotation. These patterns were compared to past studies of detailed severe weather surveys. It was observed that severe hail production was favored early in the evolution of bowing convection while severe wind production could occur throughout a storm evolution. Although tornadoes were uncommon in bowing convective systems, they tended to appear in the early-to-mature stages of evolution.
Fall 2006.
Keywords: Convection (Meteorology); Convective clouds; Severe storms -- Forecasting